Morphological Terms in the Textbooks of Morphology: A study of their concepts Overlapping and Forms substitution - Omer, Abu Haneefa Omer AlShareef Ali; ElSiddig, Entesar Mahdadi Abdallah (Arab Journal for Sciences and Research Publishing, 2019)
This study investigates practical morphology terms in the textbooks of morphology in terms of concepts overlapping and forms substitution. The main objectives are to define the terms of practical morphology as introduced by the morphologists and to investigate these terms in terms of overlapping and forms substitution showing the relationship between these terms citing from the holly Quran and the Arabic poetry. This study came up with some results most notably is that in terms of coinage and naming, practical morphology has been used by bin Malik and the basis of morphological studies is to start with its practicality before the scientific aspects and the study of morphology precedes syntax. Citing from Quran and Arabic poetry manifests a powerful relation between the adverb of place and the adverb of time from one hand, and the present participle and the gerund from the other hand.
Keywords: Morphological terminology; Practical morphology; Morphological rule; Alternation